Multiethnic Exome-Wide Association Study of Subclinical Atherosclerosis. (December 2016) - Natarajan, Pradeep; Bis, Joshua C.; Bielak, Lawrence F.; Cox, Amanda J.; Dörr, Marcus; Feitosa, Mary F.; Franceschini, Nora; Guo, Xiuqing; Hwang, Shih-Jen; Isaacs, Aaron; Jhun, Min A; Kavousi, Maryam; et al.
Abstract : Background—: The burden of subclinical atherosclerosis in asymptomatic individuals is heritable and associated with elevated risk of developing clinical coronary heart disease. We sought to identify genetic variants in protein-coding regions associated with subclinical atherosclerosis and the risk of subsequent coronary heart disease. Methods and Results—: We studied a total of 25 109 European ancestry and African ancestry participants with coronary artery calcification (CAC) measured by cardiac computed tomography and 52 869 participants with common carotid intima–media thickness measured by ultrasonography within the CHARGE Consortium (Cohorts for Heart and Aging Research in Genomic Epidemiology). Participants were genotyped for 247 870 DNA sequence variants (231 539 in exons) across the genome. A meta-analysis of exome-wide association studies was performed across cohorts for CAC and carotid intima–media thickness. APOB p.Arg3527Gln was associated with 4-fold excess CAC ( P =3×10 − 10 ). The APOE ε2 allele (p.Arg176Cys) was associated with both 22.3% reduced CAC ( P =1×10 − 12 ) and 1.4% reduced carotid intima–media thickness ( P =4×10 − 14 ) in carriers compared with noncarriers. In secondary analyses conditioning on low-density lipoprotein cholesterol concentration, the ε2 protective association with CAC, although attenuated, remained strongly significant. Additionally, the presence of ε2 was associated with reduced risk for coronary heart disease (odds ratio 0.77; P =1×10 − 11 ). Conclusions—: Exome-wide association meta-analysis demonstrates that protein-coding variants in APOB and APOE associate with subclinical atherosclerosis. APOE ε2 represents the first significant association for multiple subclinical atherosclerosis traits across multiple ethnicities, as well as clinical coronary heart disease. Abstract : Supplemental Digital Content is available in the text.